Comparative analysis of initiatives for taxation of the modern digital economy and the possible complexities arising from fundamental changes in existing taxation policies - Upītis, Andrejs (Riga Graduate School of Law, 2021)
The digital economy is growing rapidly and the modern business concepts are moving even further and further away from ‘brick and mortar’ type of businesses. The modern tech companies no longer earn their greatest profits in the place where they are registered, in fact the latest practices show that companies of the digital economy are attempting to pay as low as possible tax in the place where they are registered and earn their profits in different countries. In our lives the digital economy and such digital economy giants as Google, Facebook, Instagram and Amazon are becoming more and more present and receive our engagement more and more. For that reason it is crucial to keep these companies within certain borders and to show that the law is still above them. Each country separately is powerless against the digital economy, however if the OECD and the European Commission succeed with implementation of new taxes and tax policies then the fight against the modern day digital economy is not yet lost. If each country understands the benefits of implementation of, for example, minimum tax rate or digital service tax.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Taxation; Digital economy